Severe neonatal hypercalcemia in 4-month-old, presented with respiratory distress and chest wall deformity - Akram Aljahdali (Elsevier, 2015)
Neonatal severe hyperparathyroidism (NSHPT) is a rare disease affecting calcium metabolism and results in severe life-treating hypocalcemia of the neonates. Diagnosis can be challenging due to variable and nonspecific symptomatology. We are reporting on a 4-month-old female infant presenting with respiratory distress and chest wall deformity. We are trying to highlight different surgical options for this rare disease and importance of close collaboration with the pediatric endocrinologist in the treatment plan for those patients.